Modulation of NKG2D, KIR2DL and Cytokine Production by Pleurotus ostreatus Glucan Enhances Natural Killer Cell Cytotoxicity Toward Cancer Cells - EL-Deeb, Nehal M.; EL-Adawi, Hala I.; EL-wahab, Abeer E. Abd; Haddad, Ahmed M.; EL Enshasy, Hesham A.; He, You-Wen; Davis, Keith R. (Frontiers in Cell and Developmental Biology, 2019)
Medicinal mushrooms have been used for centuries as antitumor, antiviral, and antibacterial agents. These biological effects of mushrooms are suggested to be due to the indirect action of stimulating immune cells. The aim of this study is to investigate the possible immunomodulatory effects of mushroom polysaccharides on NK cells against different cancer cells. In this current study, fruiting bodies isolated from cultured Pleurotus ostreatus were extracted and partially purified using DEAE ion-exchange chromatography. The activation action of the collected fractions on Natural Killer cells was quantified against three different cancer cell lines in the presence or absence of human recombinant IL2 using three different activation and co-culture conditions. The possible mode of action of mushroom polysaccharides against cancer cells were evaluated at the cellular and molecular levels. Our results indicate that P. ostreatus polysaccharides induced NK-cells cytotoxic effects against lung and breast cancer cells with the largest effect being against breast cancer cells (81.2%). NK cells activation for cytokine and chemokine secretion was associated with upregulation of KIR2DL genes while the cytotoxic activation effect of NK cells against cancer cells correlated with NKG2D upregulation and induction of IFN-γ and NO production. These cytotoxic effects were attenuated in the presence of IL2. Analysis of the most active partially-purified fraction indicates that it is predominantly composed of glucans. These results indicate bioactive 6-linked glucans present in P. ostreatus extracts activate NK-cell cytotoxicity via regulation of activation and induction of IFN-γ and NO. These studies establish a positive role for bioactive P. ostreatus polysaccharides in NK-cells activation and induction of an innate immune response against breast and lung cancer cells.